2021
DOI: 10.1021/acsomega.0c05487
|View full text |Cite
|
Sign up to set email alerts
|

Resource Recycling of Mn-Rich Sludge: Effective Separation of Impure Fe/Al and Recovery of High-Purity Hausmannite

Abstract: Groundwater treatment sludge is a Fe/Mn-rich waste generated in mass production in a groundwater treatment plant for potable water production. The conventional disposal of sludge, such as direct discharge into river/lake, sea, and landfill, is not environmentally sustainable. Herein, a novel method was proposed to effectively separate Fe/Al and recover Mn via a combined hydrochloric acid leaching and hydrothermal route. The sludge contained 14.6% Fe, 6.3% Mn, and 11.5% Al and was first dissolved in 5 M HCl to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This study revealed a mean concentration of 7.82 ± 2.43 mg/kg for manganese, with concentrations ranging from 5.02 to 9.39 mg/kg. It is worth noting that there seems to be no maximum amount of Mn in biosolids because it represents a valuable micronutrient for plants, birds, and animals, and poses a low hazard to the environment [26] , [41] . Our findings indicated a lower mean concentration of Mn, compared to sewage sludge in Poland which documented concentrations between 65.43 and 224.19 mg/kg [26] .…”
Section: Resultsmentioning
confidence: 99%
“…This study revealed a mean concentration of 7.82 ± 2.43 mg/kg for manganese, with concentrations ranging from 5.02 to 9.39 mg/kg. It is worth noting that there seems to be no maximum amount of Mn in biosolids because it represents a valuable micronutrient for plants, birds, and animals, and poses a low hazard to the environment [26] , [41] . Our findings indicated a lower mean concentration of Mn, compared to sewage sludge in Poland which documented concentrations between 65.43 and 224.19 mg/kg [26] .…”
Section: Resultsmentioning
confidence: 99%